Genome-wide association study of atrial fibrillation in 114, 539 Finnish individuals reveals novel locus associated with cardiac remodelling. (14th October 2021) - Paludan-Muller, C; Vad, O B; Svendsen, J H; Olesen, M S
Abstract: Background/Introduction: Atrial fibrillation (AF) is the most common cardiac arrhythmia and it is associated with serious complications, such as stroke, heart failure, and premature death. Previous genome-wide association studies (GWAS) have associated more than 140 genomic loci with AF; however, these studies predominantly include subjects of European ancestry. Although, the Finnish population is European, it is genetically considered different from other European populations as it has been isolated and developed through multiple bottlenecks followed by population growth. Therefore, pathogenic variants are more easily discovered and heritably diseases are more prevalent. Methods: We accessed summary statistics on atrial fibrillation and flutter (I48) from the Finngen project. Loci were defined as 1 megabase regions around lead SNPs, and loci were considered novel when the SNPs had P-values <5x10 –8 after conditional analysis, and no previously reported SNPs were within the loci. FINEMAP was done with a Finnish LD reference panel, and colocalization of GWAS and eQTL signals were analysed with MetaXcan. Results: A GWAS on 17, 325 Finnish AF cases and 97, 214 controls confirms 16 previous identified loci and reveals one novel locus on chromosome 19. The novel lead SNP, rs190065070 (odds ratio [OR] = 1.44, 95% confidence interval [CI] = 1.29–1.61, P-value = 5.96x10 –11 ), is close to the gene EMC10, which encodes the endoplasmic reticulum membrane protein complex subunit 10. While the locus harbours other genes, our MetaXcan analysis could not provide conclusive evidence for other plausible genes. The EMC complex consists of 10 subunits and is a chaperone in endoplasmic reticulum-resident membrane proteins. Previous mouse studies have shown EMC10 to be important in angiogenesis after myocardial infarction, and it has recently been associated with a novel neurodevelopment syndrome. The EMC1 subunit has been associated with congenital heart disease. Conclusion: We present a novel susceptibility locus associated with AF in the Finnish population. The locus is in proximity to the gene EMC10, which is involved in structural remodelling of the heart after myocardial infarction. These results propose a potentially novel pathophysiological pathway in AF. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): The Research Foundation RigshospitaletThe John and Birthe Meyer Foundation